Proceedings of the 10th Annual Conference on Genetic and Evolutionary Computation 2008
DOI: 10.1145/1389095.1389136
|View full text |Cite
|
Sign up to set email alerts
|

Modular neuroevolution for multilegged locomotion

Abstract: Legged robots are useful in tasks such as search and rescue because they can effectively navigate on rugged terrain. However, it is difficult to design controllers for them that would be stable and robust. Learning the control behavior is difficult because optimal behavior is not known, and the search space is too large for reinforcement learning and for straightforward evolution. As a solution, this paper proposes a modular approach for evolving neural network controllers for such robots. The search space is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 25 publications
(32 reference statements)
1
36
0
1
Order By: Relevance
“…Evolutionary computation, frequently involving the evolution of neural network controllers, has been successfully used to this end [3]- [10]. Evolved gaits are often better than those produced by human designers; one was even included on the commercial release of Sony's AIBO robotic dog [3], [7]. However, many researchers have found that they cannot hand the entire problem over to evolutionary algorithms, because of the large number of parameters that need to be simultaneously tuned to achieve success [3], [7], [9]- [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evolutionary computation, frequently involving the evolution of neural network controllers, has been successfully used to this end [3]- [10]. Evolved gaits are often better than those produced by human designers; one was even included on the commercial release of Sony's AIBO robotic dog [3], [7]. However, many researchers have found that they cannot hand the entire problem over to evolutionary algorithms, because of the large number of parameters that need to be simultaneously tuned to achieve success [3], [7], [9]- [15].…”
Section: Introductionmentioning
confidence: 99%
“…Evolved gaits are often better than those produced by human designers; one was even included on the commercial release of Sony's AIBO robotic dog [3], [7]. However, many researchers have found that they cannot hand the entire problem over to evolutionary algorithms, because of the large number of parameters that need to be simultaneously tuned to achieve success [3], [7], [9]- [15]. Many of these scientists report that, while it is possible to evolve a controller to manage the inputs and outputs for a single leg, once evolution is challenged with the inputs and outputs of many legs, it fails to make progress.…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of locomotion gaits for multilegged robots is a classical problem in EC, addressed in many prior studies utilizing both direct and generative encodings (e.g., Liu and Iba (2004); Clune et al (2011);Valsalam and Miikkulainen (2008)). In the large majority of these studies, the performance of evolved individuals is analyzed solely by the walking speed of the robot and the required number of generations of evolution.…”
Section: Hexapod Locomotion Problemmentioning
confidence: 99%
“…The controller for a multilegged robot can be implemented as a system of interconnected neural network modules, each controlling a different leg [1,34]. Some of these modules and interconnections may be identical, resulting in symmetries, i.e.…”
Section: The Enso Approachmentioning
confidence: 99%